From Siraf to Sumatra seafaring and spices in the islamicate Indo-Pacific, ninth-eleventh centuries C.E. - Averbuch, Bryan Douglas (Harvard University, 2013)
This dissertation is a study of early Islamicate commerce in natural luxuries of the tropical Indian Ocean and Western Pacific Rim, such as spices, ambergris and pearls, between the ninth and eleventh centuries C.E.I approach this topic by looking at a wide array of textual sources, from geographies, anecdotes, travel narratives, inscriptions, and the records of embassies, to materia medica and the oldest surviving Islamicate cookbook. I analyze these sources alongside material culture, archeological evidence from ports in Iran, Oman, and Southeast Asia, and newly-discovered shipwrecks from the Java Sea. Adapting the work of environmental scientists to the thesis, I locate this early Islamicate commerce within a bio-geographical space, the tropical "Indo-Pacific." I argue that desires for the tropical luxuries of the environmentally-distinct Indo-Pacific helped to define the cosmopolitan culture of early Islamicate societies, from Iran and Iraq to Egypt and Spain. These desires promoted an expanding Islamicate maritime commerce across the Indo-Pacific, which led to the flourishing of port-cities in southern Iran and Oman. This maritime trade expanded Islamicate geographical horizons, as reflected in the evolving "wonders" and geographical literature of the era. It also led to early contacts between the Islamic world and the peoples of the tropical Pacific Rim, a phenomenon that contributed, in time, to the formation of Islamicate societies in maritime Southeast Asia.
Keywords: Indo-Pacific, Islam, maritime trade, Southeast Asia, spice trade
Keywords: History; Middle Eastern history; Asian history; Academic theses; Hochschulschrift